FORMING RISK-ORIENTED COMPETENCE OF MILITARY SERVICES IN CONDITIONS OF TRANSITION TO WORLD SAFETY STANDARDS - Artemov, V.; Lytvynenko, N. (Bulletin of Taras Shevchenko National University of Kyiv. Military-special sciences, 2020)
The professional training of the modern military serviceman of the Armed Forces is an ongoing process that involves the formation of a person with high moral and business qualities, capable of qualitatively solving complex military and professional tasks in peacetime and special period. The training of military personnel is carried out against the background of global confrontation and hybrid aggression by the northern neighbor. One of the important components of the Armed Forces reform is the long-awaited reform for noncommissioned officers. It is planned to change the functionality of the sergeant corps, in essence, to form the necessary risk-oriented competencies for the sergeant, to make him an effective assistant to the middle-level commander and to create additional motivation for the citizens of Ukraine to undergo military service under a contract, which will facilitate the transition of the Armed Forces of Ukraine. However, the issue of risk-oriented competency formation for military personnel in the context of the transition to global security standards has still received little attention. The purpose of the article is to create a scientific foundation for the formation of risk-oriented competence of military personnel in the conditions of transition to the world security standards. On the whole, it can be stated that the level and quality of professional training of military personnel in Ukraine is at a satisfactory level, but needs improvement. Today, the military education system has received practical training, the advanced training methods of the NATO Member States’ Armed Forces, as well as distance learning technologies have been introduced into the educational process, military education institutions are equipped with modern methods, but educational and methodological support for the risk orientation. According to current ideas, risk-based thinking and risk-oriented competence should be shared by every member of society. However, above all, this applies to those whose professional activity depends on the security of the state and society.